Controle epigenético da expressão do gene CAST, relacionado à maciez de carne em bovinos de corte - Rocha, Marina Ibelli Pereira (2013)
The Meat tenderness, a trate of economic importance in animal production, is influenced by the intensity of the degradation of myofibrillar proteins in post-mortem. The μ-calpain is the main enzyme responsible for meat tenderness of skeletal muscle, and, conversely, the calpastatin, which is encoded by the CAST gene, acts as endogenous inhibitor of calpain and thus decreases the extent of proteolysis in skeletal muscle. Polymorphisms in CAST were associated with enzyme activity and shear force, indicating the great importance of the study of CAST gene regulation. It is known that the transcription of most genes is stably suppressed in most tissues and only remains active in their tissue of expression and in certain developmental stages, and that can be controlled by epigenetic events such as methylation of DNA cytosine that is identified by sequencing of bisulfite-treated DNA. The aim of this study was to evaluate if there was preferential expression, of tissue, genotype and stage of development for the CAST gene in liver, muscle and skin of fetuses and muscle and liver of homozygous and heterozygous adult cattle for the A> G exon 30/3'UTR polymorphism, evaluated by real-time PCR with SYBR ® fluorophore, and to verify if the differential expression is regulated by the methylation status of promoter region. Differential gene expression analyses were normalized to the reference gene RPS-9. When we analyzed the tissue-specific expression in fetuses, the CAST gene was 2 times more expressed in liver than in skin (p <0.05) and almost two times more expressed in liver than in muscle (p <0.05). It was also found that this gene was 1.83 x up regulated in adult muscle when compared to fetal muscle (p <0.05), showing differential expression in the developmental stage. Differences in expression between genotypes were also found, when comparing the homozygous genotype to the heterozygous genotype (used as calibrator). Fetal samples of muscle and skin of individuals with GG genotype presented higher expression (p <0.05) of CAST gene (2x and 1,74 x, respectively, compared to heterozygous) and muscle of animals with AA genotypes also presented higher expression (1.4x compared to AG). In adult animals, the gene was up regulated in liver and muscle of individuals with GG genotype (2x and 1.63x more than AG, respectively) and was less expressed in the liver of homozygote AA (0,32x less than AG) (p <0.05). The presence of a CpG island in the promoter region of the gene CAST was identified and the methylation status was studied after bisulfite treatment, cloning of the fragment and sequencing of clones. The CpG island was hypomethylated in different tissues: 0.63% of methylated CpG dinucleotides in fetal muscle, 0.43% in fetal liver and 0.61% in adult muscle. According to the different genotypes the island was methylated in 0.61%, 0 49%, 0.60% in animal with AA genotype, 0.81%, 0.35%, 0.34% in AG, 0.4%, 0.45% ,0.9% in GG in fetal muscle, fetal liver and adult muscle respectively. In our results we show that the CpG island is hypomethylated and can allow transcription of the gene but the methylation does not explain the differences in expression within tissues, developmental stage and genotypes of the CAST gene.